Analisis Ketahanan Pangan Di Provinsi Kepulauan Bangka Belitung Tahun 2020 – 2024 - Handini, Karina Dwi; Ratmawati, Ratmawati; emilia, emilia (Poltekkes Kemenkes Pontianak, 2025)
Food security develops with the concept of ensuring that every individual and at all times can access food as the staple food needed both physically and economically. Food and nutritional security is the fourth pillar in the strategy to accelerate stunting prevention. The 2020 Food Security Index (FSI) of Provinsi Kepulauan Bangka Belitung is in the resilient category with an index of 71.21. In 2021 it has increased to 73.22 (resistant category). From 2022 to 2024 there will be a decrease respectively to 71.71, 71.14 and 70.21. This research aims to analyze the food security situation in Provinsi Kepulauan Bangka Belitung from 2020 to 2023 which includes aspects of food availability, accessibility and utilization. This research is a literature study using secondary data. The food security situation in Provinsi Kepulauan Bangka Belitung is seen based on the aspects of food availability, food acessibility and food utilization. The food availability aspect is at very vulnerable status. The food accessibility aspect is at very food secure status. The food utilization aspect is at a stable status with indicators that are still not optimal, namely the average length of schooling for women of more than 15 years and the prevalence of stunting.